CGIAR Food Systems Accelerator Entrepreneur Spotlight: Afri-Farmers Market – Leveraging Technology to Empower Rural Farmers - Zulu-Hume, Mercy F. (CGIAR System Organization, 2023)
A blog profiling the Afri-Farmers Market which is one of the agribusinesses that the CGIAR Food Systems Accelerator (CFSA) is supporting to scale climate-smart innovations that address food system challenges.